Reservoir characterization using laboratory ultrasonic rock physics: understanding pore fluid effects on elastic properties - Shodunke, Ganiyat Oluwaseun (Kansas State University, 2021)
The quantity of hydrocarbon recovered from a carbonate reservoir varies depending on the quality (i.e., porosity, permeability, reservoir volume) of that reservoir, indirectly characterized from the elastic properties encoded in the seismic reflection data. Due to the complexity of carbonates, they require repeated updating of characterization and modeling during production. This creates added cost to well drilling but provides significant return in terms of decisive field development plans and knowledge of productive and nonproductive hydrocarbon zones. The purpose of this study is to understand the effects of pore-fluid composition on the elastic properties of the Viola formation reservoir found in Kansas, Oklahoma, and Texas, and implications for utilization of seismic data attributes in optimizing reservoir studies and guiding field development efforts. Rock physics experiments such as lab ultrasonic experiments and fluid replacement experiments integrated with seismic fluid replacement modeling were used to pursue a thorough understanding of the carbonate reservoir properties. Brine, oil, and water were injected into the carbonate rock during the fluid replacement experiment and ultrasonic waves were propagated through the rock to obtain Primary P wave velocity, Secondary S wave velocity, and elastic parameters such as Young’s modulus, Shear (Rigidity) modulus, Bulk modulus, and Poisson’s ratio. These parameters were also recorded for the rock under dry conditions, and they provided useful information about the seismic wave’s response to fluids and lithofacies changes in the Viola carbonate rock. There was a noticeable response change in amplitude and some change in velocity and impedance of the wave traveling through the Viola limestone formation with the presence of and type of fluid present. Higher amplitudes and faster velocities were observed for dry rock wave signals, while lower amplitudes and slower velocities were recorded for brine and oil-saturated rock wave signals. The recorded results on the Viola cores were in accordance with previously observed Gassmann fluid replacement modeling results (Cimino, 2020) from the Viola well log data and seismic amplitude analysis (Vohs, 2016) from the Viola seismic data.
Keywords: Viola limestone formation; Rock physics; Fluid replacement experiments; Ultrasonic velocity experiment; Attenuation; Comanche County, Kansas